Optimal multibinding unification for sharing and linearity analysis. Issue 3 (May 2014) - AMATO, GIANLUCA; SCOZZARI, FRANCESCA
Abstract In the analysis of logic programs, abstract domains for detecting sharing properties are widely used. Recently, the new domain <alternatives><inline-graphic xlink:href="ark:/27927/pgg5h7x0wnb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[ShLin^ω]]> </alternatives> has been introduced to generalize both sharing and linearity information. This domain is endowed with an optimal abstract operator for single-binding unification. The authors claim that the repeated application of this operator is also optimal for multibinding unification. This is the proof of such a claim.